The Authority of the International Court of Justice in Islamic Jurisprudence: Fatwas on Genocide and War Crimes in Bosnia and Herzegovina (Context: Journal of Interdisciplinary Studies, 2024)
This article explores how the authority of the International Court of Justice (ICJ) is perceived in fatwas on genocide and war crimes committed in Bosnia and Herzegovina during the 1992-1995 war. Sources include the ICJ’s judgement in Bosnia and Herzegovina v. the Federal Republic of Yugoslavia (Serbia and Montenegro); verdicts of the International Criminal Tribunal for the Former Yugoslavia; two fatwas from the Islamic Community in Bosnia and Herzegovina’s Council of Muftis on war crimes against the Bosniak populations of Srebrenica, Žepa, Prijedor and the Sana Valley; and preparatory materials written by expert groups that preceded the fatwas’ issuance. Despite initial criticism of the localisation of genocide in the ICJ’s judgement, the fatwas recognise its authority in cases that apply the Genocide Convention. The argumentation of these fatwas is based on the higher objectives of Islamic law (maqasid al-Sharia), in accordance with the role of Islamic normativity in a secular state.